2006
DOI: 10.1186/1471-2199-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Competition between the DNA unwinding and strand pairing activities of the Werner and Bloom syndrome proteins

Abstract: BackgroundThe premature aging and cancer-prone Werner and Bloom syndromes are caused by defects in the RecQ helicase enzymes WRN and BLM, respectively. Recently, both WRN and BLM (as well as several other RecQ members) have been shown to possess a strand annealing activity in addition to the requisite DNA unwinding activity. Since an annealing function would appear to directly oppose the action of a helicase, we have examined in this study the dynamic equilibrium between unwinding and annealing mediated by eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 25 publications
1
73
0
Order By: Relevance
“…Un-annealed regions are in boldface. ing of single-stranded DNA in the presence of annealing advocates Werner protein and BLM (34). Our results demonstrate that RPA promotes strand unwinding as well.…”
Section: Resultssupporting
confidence: 53%
“…Un-annealed regions are in boldface. ing of single-stranded DNA in the presence of annealing advocates Werner protein and BLM (34). Our results demonstrate that RPA promotes strand unwinding as well.…”
Section: Resultssupporting
confidence: 53%
“…Besides helicase activity, several recent studies showed enhanced complementary DNA strand annealing by BLM and other RecQ helicases. Such activity has been demonstrated for BLM (9), WRN (10,11), RecQ5β (12), and RecQ1 (13). Strand annealing occurs most efficiently in the absence of ATP and is inhibited by single-strand binding proteins (SSBs) such as Replication Protein A (RPA) and SSB.…”
Section: Introductionmentioning
confidence: 87%
“…Where it has been mapped, this SA activity localizes to a region C-terminal of the core helicase domain near the less well-conserved RQC and HRDC domains (e.g., BLM residues 1290–1350) [36, 38]. This SA activity is inhibited by ATP and non-hydrolyzable nucleotide analogs [3436, 38, 39] as well as by the ssDNA binding protein, Replication Protein A (RPA) [34, 36, 38, 40]. RPA is known to functionally interact with and stimulate the DNA helicase activity of BLM and WRN [4043] where it binds through its 70 kDa subunit to the N-terminus of WRN and BLM [44].…”
Section: Introductionmentioning
confidence: 99%